Cell-penetrating TLR inhibitor peptide alleviates ulcerative colitis by the functional modulation of macrophages - Thapa, Bikash; Pak, Seongwon; Chung, Dohyeon; Shin, Hye Kyoung; Lee, Seong Ho; Lee, Keunwook (Frontiers in Immunology, 2023)
Toll-like receptors (TLRs) have a crucial role not only in triggering innate responses against microbes but in orchestrating an appropriate adaptive immunity. However, deregulated activation of TLR signaling leads to chronic inflammatory conditions such as inflammatory bowel disease (IBD). In this study, we evaluated the immunomodulatory potential of a TLR inhibitor in the form of a cell-penetrating peptide using an ulcerative colitis animal model. A peptide derived from the TIR domain of the TLR adaptor molecule TIRAP that was conjugated with a cell-penetrating sequence (cpTLR-i) suppressed the induction of pro-inflammatory cytokines such as TNF-alpha and IL-1beta in macrophages. In DSS-induced colitis mice, cpTLR-i treatment ameliorated colitis symptoms, colonic tissue damage, and mucosal inflammation. Intriguingly, cpTLR-i attenuated the induction of TNF-alpha-expressing proinflammatory macrophages while promoting that of regulatory macrophages expressing arginase-1 and reduced type 17 helper T cell (Th17) responses in the inflamed colonic lamina propria. An in vitro study validated that cpTLR-i enhanced the differentiation of monocyte-driven macrophages into mature macrophages with a regulatory phenotype in a microbial TLR ligand-independent manner. Furthermore, the cocultivation of CD4 T cells with macrophages revealed that cpTLR-i suppressed the activation of Th17 cells through the functional modulation of macrophages. Taken together, our data show the immunomodulatory potential of the TLR inhibitor peptide and suggest cpTLR-i as a novel therapeutic candidate for the treatment of IBD.